FRP as strengthening material for Reinforced Concrete beams with openings - A review - Chin, Siew Choo; Shafiq, Nasir; Nuruddin, Muhd Fadhil
This paper presents the review of studies performed to investigate the behavior of Reinforced Concrete (RC) beams containing different types of openings. For the last 4 decades, research works involved the investigation of the member strength and development of the design approach for simply supported, continuous and T-beams containing large rectangular openings subjected to torsion, bending and shear forces. The proposed design method suggested the installation of diagonal steel reinforcement bars around the opening for providing the required strength. In recent years, Fiber Reinforced Polymers (FRP) have been widely used as an external bonded reinforcement system for upgrading and retrofitting of concrete structures. FRP as externally bonded reinforcement mainly used to repair and retrofit the damaged reinforced concrete member. However, very limited studies showed the application of the FRP laminates as external reinforcement around openings. Therefore, further investigations regarding the application of FRP laminates to strengthen the large openings in reinforced concrete members are very vital.